Trombose venosa da veia subclávia após fratura de clavícula: relato de caso - Terra, Bernardo Barcellos [UNIFESP] (2011)
Deep vein thrombosis in the upper limbs is uncommon in the orthopedic literature. We report on a case of subclavian vein thrombosis that occurred during conservative treatment of a fracture in the middle third of the clavicle. This is difficult to diagnose and requires a high degree of suspicion. Treating it may prevent fatal thromboembolism. In some rare cases, it has been described in association with fractures of the clavicle.